CIFOR research: forest products and people, rattan issues - Belcher, B. (Food and Agriculture Organization of the United Nations, 2002)
The Forest Products and People programme (FPP) of the Centre for International Forestry Research (CIFOR) undertakes research to better understand the true role of non-timber forest products as tool to achieve development and conservation goals. The programme is undertaking an international comparative analysis of cases of forest product development, and a series of thematic case-based research projects designed to answer specific questions. An example is provided from a case study in East Kalimantan, Indonesia, where a traditional rattan cultivation system has been severely stressed by a combination of policy and economic factors. Government policies designed to encourage the domestic processing industry and monopsonistic manufacturing association have sharply depressed demand and prices. Other factors such as development of roads, industrial plantations, mining, and other economic activities offered alternatives that have led some rattan farmers to shift to new activities. And, recent wide spread of forest fires have destroyed large areas of rattan gardens, effectively forcing some rattan farmers out of business. This set of conditions offers a good opportunity to study people's responses and to analyse wheter and under what circumtances this particular intermediate forest product management system is a viable economic option now and in the future. As rattan remains an important commodity in Indonesia and internationally, and as the current farm-gate price for rattan appears to be artificially low, due in large part to the prevailing policy environment, the rattan garden system may remain viable, at least in the medium term.